Paws. 1, Gabby gets it together - Fairbairn, Nathan; Assarasakorn, Michele (New York : Razorbill, 2022)
Best friends Gabby, Priya and Mindy create a dog walking business, and quickly learn that running a business is no walk in the park.
School Library Journal starred, January 2022
Horn Book, March 2022
3-6
3.3
Keywords: Dogs -- Comic books, strips, etc. -- Juvenile fiction; Money-making projects for children -- Comic books, strips, etc. -- Juvenile fiction; Best friends -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Dogs -- Fiction; Moneymaking projects -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Cartoons and comics; Graphic novels; Comics (Graphic works)